1993
DOI: 10.1037/0033-2909.113.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral correlates of individual differences in road-traffic crash risk: An examination of methods and findings.

Abstract: This article considers methodological issues relevant to the study of differential crash involvement and reviews the findings of research in this area. Aspects of both driving skill and driving style appear to contribute to crash risk. Of the former, hazard-perception latency appears to play an important role, and this may be attributable to generalized abilities to identify visual targets in a complex background and to switch attention rapidly. Of the latter, faster driving speed and willingness to commit dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
313
3
26

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(357 citation statements)
references
References 105 publications
(152 reference statements)
15
313
3
26
Order By: Relevance
“…Correlations reported in the literature between annual mileage and accidents are in the range of 0.12-0.35 [3]. At the same time it has been shown that high-mileage drivers have lower accident risk per mile driven than low-mileage drivers [4].…”
Section: Introductionmentioning
confidence: 92%
“…Correlations reported in the literature between annual mileage and accidents are in the range of 0.12-0.35 [3]. At the same time it has been shown that high-mileage drivers have lower accident risk per mile driven than low-mileage drivers [4].…”
Section: Introductionmentioning
confidence: 92%
“…The other studies also found the strong relationship between the driver' speed behavior and accidents [2]- [6]. There are two separate components which affect human factors in driving, driving skills and driving style [7]. Driving style has a direct relation to the individual drivers' behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, although several reasons may explain the prevalence of self-reports , questions about their veracity and accuracy have been raised (see Elander et al, 1993;Harano, Peck, & McBride, 1975;Loftus, 1993). Consequently, archival data have been considered as an alternative to self-reports.…”
Section: Introductionmentioning
confidence: 99%